The NLRP3 inflammasome is a potential mechanism and therapeutic target for perioperative neurocognitive disorders - Li, Jiayue; Li, Li; He, Jiannan; Xu, Jianhong; Bao, Fangping (Frontiers in Aging Neuroscience, 2023)
Abstract Perioperative neurocognitive disorders (PNDs) are frequent complications associated with cognitive impairment during the perioperative period, including acute postoperative delirium and long-lasting postoperative cognitive dysfunction. There are some risk factors for PNDs, such as age, surgical trauma, anesthetics, and the health of the patient, but the underlying mechanism has not been fully elucidated. Pyroptosis is a form of programmed cell death that is mediated by the gasdermin protein, and it is involved in cognitive dysfunction disorders. The canonical pathway induced by nucleotide oligomerization domain (NOD)-, leucine-rich repeat (LRR)- and pyrin domain-containing protein 3 (NLRP3) inflammasomes contribute to PNDs, which suggests that targeting NLRP3 inflammasomes may be an effective strategy for the treatment of PNDs. Therefore, inhibition the upstream activators and blocking the assembly of the NLRP3 inflammasome may attenuate PNDs. The present review summarizes recent studies and systematically describes the pathogenesis of NLRP3 activation and regulation and potential therapeutics targeting NLRP3 inflammasomes in PND patients.